Поведение кислорода и азота в расплаве в процессе кислородно-конвертерной плавки - Семыкин, С.И.; Тубольцев, Л.Г.; Корченко, В.П. (Фундаментальные и прикладные проблемы черной металлургии, 2017)
В работе выполнено сравнение эффективности различных технологий и вариантов кислородно-конвертерной плавки по возможности достижения минимального содержания кислорода и азота в стали. Выявлено влияние вариантов кислородно-конвертерной плавки с верхней и комбинированной продувкой на содержание газов в расплаве, что позволяет ранжировать технологии и определять области их возможного применения. Показано, что технология верхней продувки кислородом по наложению электрических потенциалов позволяет уменьшить содержание кислорода в расплаве на 40-70%, а азота - на 25-40%. В роботі виконано порівняння ефективності різних технологій і варіантів киснево-конвертерної плавки по можливості досягнення мінімального вмісту кисню та азоту в сталі. Виявлено вплив варіантів киснево-конвертерної плавки з верхньою та комбінованою продувкою на вміст газів у розплаві, що дає змогу ранжувати технології і визначати області їх можливого застосування. Показано, що технологія верхньої продувки киснем з накладенням електричних потенціалів дає змогу зменшити вміст кисню у розплаві на 40-70%, а азоту - на 25-40%. In this paper, the efficiency of different technologies and varieties of oxygenconverter heat has been compared with the aim to achieve the minimum content of oxygen and nitrogen in steel. The quantitative estimation for the technology efficiency has been carried out with the use of the relation of gases in the melt to their equilibrium content at equal carbon contents. The paper reveals the influence of production technology with the combined blowing on the content of gases in the melt. It allows decreasing oxygen content in the metal, however, its influence on the nitrogen content is not simple: nitrogen content can decrease or increase and the determining factor here is the type of the gas introduced from the bottom. The technology of upper blowing with oxygen along with electric potentials application permits the 40-70 % decrease in oxygen within the melt while nitrogen can be 25-40% less.